An Overview of Wax Crystallization, Deposition Mechanism and Effect of Temperature & Shear - Azwan, Harun; Nik Khairul Irfan, Nik Ab Lah; Hazlina, Husin; Zulkafli, Hassan (IEEE, 2016)
Wax deposition can cause serious problem to crude oil transportation especially in offshore transport pipelines. It is cause by the heat transfer between the crude oil and the surrounding if there is no or insufficient thermal insulation layer coating on the pipeline. Cause of the wax deposition in the pipeline will lead to a smaller flow diameter of the pipeline, thus will results in flow restriction and production loss. This paper will explain briefly how wax started to form deposits base on crystallization theory. Besides that, this paper will review some of the proposed mechanisms of wax deposition such as molecular diffusion, soret diffusion, shear dispersion, brownian diffusion and gravity settling. Furthermore, the effects of temperature and shear towards wax deposition on internal surface of the pipeline are discussed.